Effectiveness of Acupuncture Care In Cases of Sided Facial Paralysis (Miantan): A Case Study At The Integration Polyclinic of Carolus Borromeus Hospital, Kupang, NTT - Vivi Kurniati Tjahjadi; Mayang Wulandari; Amal Prihatono (International Journal of Health and Pharmaceutical (IJHP), 2026)
Unilateral facial paralysis, also known as Miantan, refers to paralysis affecting one side of the face. One type of Miantan is Shi Syndrome, which is caused by pathogenic factors such as wind-cold and wind-heat. These factors lead to obstruction of the flow of Qi in the Yang Ming and Shao Yang meridians, resulting in a “wind-phlegm” syndrome. This condition manifests with various associated symptoms, including weakness of the facial muscles, and may lead to the characteristic clinical features of Bell’s palsy. Bell’s palsy is a peripheral facial nerve paralysis characterized by weakness or paralysis on one side of the face due to dysfunction of the seventh cranial nerve. This condition is characterized by inability to close the eyes completely, drooping of the mouth corner, and facial asymmetry. This study aimed to determine the effectiveness of acupuncture care in patients with Bell’s palsy at the Integrative department of St. Carolus Borromeus Hospital Kupang. This study used a qualitative case study design. The participant was a 35-year-old female patient diagnosed with left-sided Bell’s palsy. Data were collected using acupuncture diagnostic methods including observation (Wang), listening and smelling (Wen), questioning (Wen), and palpation (Qie). Acupuncture therapy was administered based on the established diagnosis of disease and syndrome. The results showed facial asymmetry on the left side, inability to raise the forehead, and incomplete eyelid closure. After several acupuncture therapy sessions, improvements were observed in facial muscle function, eyelid closure ability, and facial expressions. This study concludes that acupuncture therapy can improve facial nerve function and accelerate recovery in patients with Bell’s palsy.